Metabolic bioprofiling of different Glycyrrhiza glabra solvent fractions for the identification of anti-adenoviral compounds using LC-HRMS/MS and in-vitro cytopathic assay coupled with chemometry - Rahma SR. Mahrous; Hoda Fathy; Reham S. Ibrahim (BMC, 2023)
Abstract Human adenovirus type-7 (HAdV-7) is a common pathogen that may cause significant morbidity as well as severe complications. Currently, there is no approved drug for the treatment of HAdV-7 infections and the contemporary strategy mainly rely on nonspecific antivirals. Glycyrrhiza glabra; (licorice), is a well-recognized edible plant used in food and beverages. The plant is renowned for its pharmacological and biological activities including antiviral activities against wide range of viruses. The following study reported for the first time the anti-adenoviral activity of licorice extract using in-vitro cytopathic inhibitory assay. Different solvent fractions showed promising activity with IC50 reaching 1.431 μg/ml. Certain fractions had selectivity index (SI) greater than 10 indicating their efficacy together with relatively low cytotoxic effect. Metabolic profiling using LC-HRMS/MS resulted in identification of 41 compounds from licorice fractions. Chemometric modeling using Orthogonal Projections to Latent Structures (OPLS) suggested the compounds; kaempferol-3-O-rutinoside, violanthin, rhamnoliquiritin, isoliquiritigenin isomer, licoagroside B and liquiritin apioside as potential markers against (HAdV-7). Finally, kaempferol-3-O-rutinoside was further confirmed via in-vitro adenovirus inhibitory assay to possess strong antiviral activity with IC50 and CC50 of 54.7 ± 1.93 μM and 655.7 ± 2.22 μM, respectively.